2008
DOI: 10.1080/13561820802355615
|View full text |Cite
|
Sign up to set email alerts
|

The university/community partnership: Transdisciplinary course development

Abstract: This paper describes the process of expanding the knowledge base and clinical practice for students in professional preparation programs in social work, nursing and education. Through a partnership of university faculty and administrators of a private school for students with learning and behavior problems, a transdisciplinary course was designed to address the need for providing future professionals an opportunity to understand multiple perspectives in the design of clinical interventions.The process of defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…31 However, studies have shown that program evaluations by stakeholders have contributed to the improvement of programs in different aspects and have made the programs more responsive to the needs and expectations of the society in question. [31][32][33][34][35] To develop traditional nutrition and intercultural communication skills, particularly during the internship period, modules containing expeditions to different regions were recommended. 36 In a study suggesting problem-focused teaching methods aimed at professional endeavours' life, the methods that focused on problem-solving, which should be included in such programs, were noted to better prepare dietitians for their professional lives.…”
Section: Discussionmentioning
confidence: 99%
“…31 However, studies have shown that program evaluations by stakeholders have contributed to the improvement of programs in different aspects and have made the programs more responsive to the needs and expectations of the society in question. [31][32][33][34][35] To develop traditional nutrition and intercultural communication skills, particularly during the internship period, modules containing expeditions to different regions were recommended. 36 In a study suggesting problem-focused teaching methods aimed at professional endeavours' life, the methods that focused on problem-solving, which should be included in such programs, were noted to better prepare dietitians for their professional lives.…”
Section: Discussionmentioning
confidence: 99%
“…Un segundo factor, se deriva de la globalización la cual ha propiciado una mayor internacionalización de la educación superior (Bartell, 2003;Harris, 2009) mediante intercambios y estancias académicas e incluso a través del uso de las tecnologías de la información y la comunicación (Pursula, Warstat y Laaksoneni, 2005). Un tercer factor, se debe a la complejización de las disciplinas dados los avances tecnológicos acaecidos en las últimas décadas y la propia naturaleza de los problemas por resolver los cuales demandan la fertilización cruzada de varios campos disciplinarios produciendo saberes inter y transdisciplinarios (Carroll et al, 2014;Tourse et al, 2008), alentando ciertos procesos que podríamos denominar de desespecialización, es decir, cada vez se requiere dominar múltiples lenguajes disciplinarios a fin de abordar problemas complejos. Un cuarto factor se observa en el aumento de la credencialización (Stiglitz, 1975) la cual se utiliza como un medio para seleccionar a los egresados en un mercado laboral altamente competido.…”
Section: El Auge Del Posgradounclassified
“…The reasons for this are numerous, including such barriers as administrative and resource differences between various education departments, and logistical difficulties in scheduling students with different timetables to be in the same place at the same time [6] . Furthermore, a strong culture of uni-professional education has existed until now.…”
Section: Introductionmentioning
confidence: 99%